Muscle transcriptome provides the first insight into the dynamics of gene expression with progression of age in sheep - Reena Arora (Nature Portfolio, 2021)
Abstract The dynamic synergy of genes and pathways in muscles in relation to age affects the muscle characteristics. Investigating the temporal changes in gene expression will help illustrate the molecular mechanisms underlying muscle development. Here we report the gene expression changes in skeletal muscles through successive age groups in Bandur, a meat type sheep of India. RNA sequencing data was generated from the longissimus thoracis muscles from four age groups, ranging from lamb to adult. Analysis of 20 highest expressed genes common across the groups revealed muscle protein, phosphorylation, acetylation, metal binding and transport as significant functions. Maximum differentiation was observed after 2.5–3 years on transition from lambs to adult. Transcriptional regulation by the TFAP2 transcription factors, IL-6 signaling and PI3K/AKT signaling pathways were enriched in younger animals. The gene-protein network demarcated key interactive genes involved in muscle development and proliferation that can be used as candidates for future research on improvement of muscle characteristics.